Role of Women Farmer Representatives in Decision Making Bodies of ATMA - N. Balasubramani; K Uma Rani; Swati Shah (Journal of Agricultural Extension Management, 2015)
As women farmers are identified as an important link in the development of agriculture, extension reforms is one of the special interventions by the Government of India to mainstream gender in agricultural extension. The present study was planned with the objectives of understanding the processes adopted for identifying the extension needs of women farmers, examine the role played by women farmer representatives in decision making bodies of ATMA and identify the constraints faced by women farmer representatives in participating in decision making bodies of ATMA. The study was carried out in six states namely Jharkhand, Maharashtra, Madhya Pradesh, Assam, Uttarakhand and Andhra Pradesh. Three types of respondents, viz., women farmers, women farmer representatives and extension functionaries were selected for the study with a sample size of 457, 36 and 36 respectively. It was found that women farmer representatives were the main source of information for identifying the extension needs of women farmers, followed by women groups and scientists/experts. Further, women farmers revealed that their extension needs were asked during the different extension activities conducted by ATMA. It was observed that extension functionaries gave more emphasis on small and marginal women farmers while prioritizing fund allocation. The women farmer representatives have facilitated the extension functionaries in identification of extension needs and problems of the women farmers, facilitated in the planning process and implementation of extension activities. The active role played by women representatives helped in mainstreaming women in agricultural extension. However, their participation and active involvement can be further improved by addressing the constraints expressed by them.